Novel Microbial-Based Immunotherapy Approach for Crohn's Disease - Sutcliffe, Simon; Kalyan, Shirin; Pankovich, Jim; Chen, Jenny M. H.; Gluck, Rashieda; Thompson, Darby; Bosiljcic, Momir; Bazett, Mark; Fedorak, Richard N.; Panaccione, Remo; Axler, Jeffrey; Marshall, John K.; et al. (Frontiers in Medicine, 2019)
Background: Current Crohn’s disease (CD) therapies focus on suppressing immune function and come with consequent risk, such as infection and cancer. Notwithstanding, most CD patients still experience disease progression. There is a need for new CD treatment strategies that offer better health outcomes for patients. Aims: To assess safety, efficacy, and tolerability of a novel microbial-derived immunotherapy, QBECO, that aims to restore rather than suppress immune function in CD. Methods: A randomized, double-blind, placebo-controlled trial was conducted in 68 patients with moderate-to-severe CD. Primary endpoints: safety and Week 8 clinical improvement. Secondary endpoints: Week 8 clinical response and remission. Week 8 responders continued blinded treatment through Week 16; non-responders received open-label QBECO from Weeks 9-16. Exploratory analyses included immune biomarker and genotype assessments. Results: QBECO was well tolerated. Mean reduction in Crohn’s Disease Activity Index (CDAI) score was -68 for QBECO versus -31 for placebo at Week 8. Improvement with QBECO continued through Week 16 (-130 CDAI reduction). Week 8 QBECO clinical response, improvement and remission rates were 41.2%, 32.4%, 29.4% versus 26.5%, 23.5%, 23.5% for placebo. TNFα inhibitor-naïve subjects achieved higher response rates at Week 8 with QBECO (64%) versus placebo (26%). Specific immune biomarkers were identified that linked to QBECO response. Conclusion: This proof-of-concept study supports further investigation for the use of QBECO as a novel immunotherapy approach for CD. Biomarker analyses suggests it may be feasible to personalize CD treatment with QBECO. Larger trials are now needed to confirm clinical improvement and the unique biological findings.